First-to-invent versus first-to-file: International patent law harmonization and innovation - Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
The U.S. has been under pressure to abandon the unique first-to-invent feature of its patent law for awarding patents. The opposition to reform however argues that switch to a first-to-file rule, the international norm, will undermine innovation. We evaluate this argument in a dynamic stochastic model of a patent race. The result generally supports the opposition's argument.
Keywords: L3; O31; O34; 330; first-to-file; first-to-invent; patent law harmonization; innovation; U.S. patent law; Internationales Patentrecht; Rechtsangleichung; Innovationswettbewerb; Patentrecht; USA; Dynamisches Modell; Theorie